Augustine of Hippo and the tehom-Abyssus (or the darkness covering the abyss) (Circe de clásicos y modernos, 2019)
This paper dealt with the reading of postmodern thinkers in issues raised by Augustine. Analysed as Augustine in the Confessiones values to the word Tehom-abyssus of Genesis, since it considers it positive when used to imagine the world as a spongy body surrounded of God, but negative when using it to refer to the original fall of the angels and of human beings, with the subsequent rescue of the spirit through the waters of baptism. This term has allowed Augustine expressed his own interiority and aspects of the cosmos where is reflected both in its own condition as redeemed sinner. We also refer to their intense pursuit of wisdom, whose femininity reflects the femininity of Monica, which is presented by Augustine as a model of wise woman.
Keywords: Agustine; tehom-Abyssus; postmoderns; subjectivity; wisdom; evil